Διερεύνηση του μόνιμου και μη μονίμου πεδίου ροής της αεροτομής ΝΑCA 0012 - Κουμρόγλου, Βασίλης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Ναυτικής και Θαλάσσιας Υδροδυναμικής, 2018)
High Reynolds number flow over a NACA 0012airfoil in respect with the angle of attack is investigated by two dimensional computations. The fundamental time averaged Navier-Stokes equations are solved via the finite volume method. The numerical code is validated extensively at the steady state condition and fully turbulent flow regime. The angle of attack ( a:A.O.A - the angle that is formed between the chord of the airfoil and the free stream velocity) is examined at a wide range of values that includes from 0 to18 degrees for the steady state condition and from 0 to 20 degrees for the unsteady one. The flow isexamined for Reynolds 3∙10^6 which based on the existing literature we know it is a transitional flow. The turbulent nature of the flow is approached by the well validated SST k-ω model introduced by Menter , which when it is combined with the fine meshes we provide for the steady and unsteady simulation it can resolve fully the turbulent boundary layer. This model was chosen based on reports from the literature that it is the most appropriate for this kind of flow. Special attention is focused on whether the flow reaches a steady state or no. In total 6 separate unsteady simulations where conducted. Two of them where used to investigate the time independency of the flow in terms of the angle of attack in which the results have revealed the stabilization of the acting forces, thus indicated a flow field with suppressed vortex shedding activity . While four where conducted at fully unsteady flow regime so we can investigate the conditions that arise on these occasions. Increased vorticity is found to be confined to a region near the airfoils surface at an area which seems to be the origin of the creation of the vortex street and also within the turbulent boundary layer . Viscous lift is found to be neglible compared to pressure lift. On the contrary the viscous drag could reach 80% of the total drag. The magnitude of the lift and drag coefficients is affected with the change of the angle of attack. It can beclearly seen as expected from experimental data that lift values are directly proportional to the change of the angle of attack while the drag values follow a parabola like change until we reach a=16 after which the results change drastically. The magnitude of the turbulent kinetic energy is directly dependent from the angle of attack while as the latter increases also does the first. The regions that are affected by turbulence coincide with the ones that are affected by vorticity.